Legal Protection For Consumers In Online Transactions Involving Counterfeit Branded Bags: A Review Based On Law Number 8 Of 1999 Concerning Consumer Protection - Ferdy Chalik; Dina Andiza; Bambang Fitrianto (CERED Indonesia Institute, 2024)
The development of online transactions has made it easier for consumers to buy various products, including branded bags. However, this also increases the risk of the circulation of fake branded bags which is detrimental to consumers. Many buyers are deceived by cheaper prices and inaccurate information from sellers. Based on Law Number 8 of 1999 concerning Consumer Protection, consumers have the right to obtain goods that match the description and the right to compensation if a violation occurs. Therefore, this study aims to examine the legal regulations and legal protection efforts for consumers in online transactions of fake branded bags. This study uses a normative legal research method with a descriptive-analytical approach. Data were collected through a literature review covering primary, secondary, and tertiary legal materials, then analyzed qualitatively to understand the application of legal protection in online transactions. The results of the study show that although there are regulations governing consumer protection, their implementation still faces obstacles such as weak supervision of online transactions and a lack of consumer awareness of their rights. Consumers who are victims can file a complaint with the Consumer Dispute Resolution Agency (BPSK), file a civil lawsuit, or report to the authorities. To create a safer and fairer online trading ecosystem, there needs to be increased supervision, consumer education, and more specific regulations related to digital trading. In addition, law enforcement against business actors selling counterfeit goods must be tightened, so that it can provide a deterrent effect and ensure that consumer rights can be protected effectively.